2006
DOI: 10.1007/s00408-005-2561-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant–Antioxidant Balance in Patients with COPD

Abstract: The goal of this study was to evaluate the role of oxidant-antioxidant balance in the pathogenesis of COPD. We included 30 healthy nonsmokers [24 male, 6 female; mean age (yr) +/- SD: 62.4 +/- 9.3], 30 healthy smokers [27 male, 3 female; mean age (yr) +/- SD: 58.7 +/- 6.0], 71 patients with stable COPD [68 male, 3 female; mean age (yr) +/- SD: 63.5 +/- 7.9], and 31 patients with COPD exacerbation [30 male, 1 female; mean age (yr) +/- SD: 64.2 +/- 7.3]. In all study groups the peripheral venous blood samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 16 publications
4
33
0
1
Order By: Relevance
“…The failure to demonstrate significant differences in erythrocyte SOD activity between current smokers and ex-smokers in the present study, and between life-long nonsmokers and ever smokers in a previous study [16], are consistent with another published report [23]. The present findings suggest that COPD patients do not show altered erythrocyte SOD activity, contrary to the findings of previous studies [23,24] but in agreement with more recent reports [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…The failure to demonstrate significant differences in erythrocyte SOD activity between current smokers and ex-smokers in the present study, and between life-long nonsmokers and ever smokers in a previous study [16], are consistent with another published report [23]. The present findings suggest that COPD patients do not show altered erythrocyte SOD activity, contrary to the findings of previous studies [23,24] but in agreement with more recent reports [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…23 Lipid peroxidation is the oxidation reaction between ROS and polyunsaturated fatty acids, which eventually causes changes in the structure and permeability of the lung membrane. 24 The second biomarker, 8-oxo-7,8-dihydro-2Ј-deoxyguanosine, is primarily involved in DNA damage. The mechanism for this damage is the guanine:cytosine to adenine:thymine transversion on DNA replication, 25 which induces microsatellite instability and abnormal apoptosis or necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that oxidative stress is an important physiopathological change in COPD. Hanta et al measured erythrocyte superoxide dismutase enzyme activity and plasma malonyldialdehyde levels in 162 subjects (30 healthy nonsmokers, 30 healthy smokers, 71 patients with stable COPD, and 31 patients with COPD exacerbation) (36). They found that the healthy smokers and stable and exacerbated patients with COPD had an impairment in the oxidant-antioxidant balance.…”
Section: Total Oxidant Statusmentioning
confidence: 99%